KEYNES A NEOKEYNESIŚCI - Bludnik, Izabela (Wydział Prawa i Administracji UAM, 2004)
During the 1970s the early Keynesian system was abandoned following the return of the micro-foundations. Some of them, however, turned out to be overidealistic (e.g. the market-clearing price). The new ideas, developed in the 1980s and 1990s, inaugurated the “Keynes after Lucas” age. Nevertheless, the New Keynesians are, admittedly, a very heterogeneous group, difficult to describe by means of a specific, unique definition. Furthermore, modern Keynesian economics differs significantly from both Keynes’ approach and the old, orthodox Post Keynesian school. Hence, it seems necessary to investigate where the similarities between Keynes and his followers start and end. The analysis of micro-foundations, rigidities, unemployment, expectations, money and monetary policy, fiscal policy and budget deficit, shows that a very general view of Keynes’ writings still comes into consideration. But at the same time New Keynesians decidedly reject many typical, old Keynesian opinions, approving several New Classical and Monetarist suggestions. Most certainly the spirit of Keynes is recovered and New Keynesians are inheritors of the considerable part of his proposals. However, Keynes most probably would not be a New Keynesian.
KEYNES AND NEW KEYNESIANS